THE PHRASEOLOGICAL WORLDVIEW AS AN OBJECT OF LINGUOCULTUROLOGY - Bahora Juraholova Kurbonboyevna (Bright Mind Publishing, 2025)
This article explores the linguistic and cognitive functions of phraseological units and conceptual metaphors, with a focus on their role in shaping the linguistic worldview. Phraseologisms are described as fixed linguistic expressions with semantic unity, commonly used in colloquial and literary speech. Using the Uzbek verb o‘lmoq (“to die”) as a case study, the article demonstrates how phraseological euphemisms vary across stylistic registers, from everyday speech to poetic and religious language. The second part of the article delves into Conceptual Metaphor Theory (CMT), initiated by George Lakoff and Mark Johnson, and examines how abstract concepts (e.g., time, emotion, communication) are understood through metaphorical mappings from more concrete domains (e.g., fire, movement, journey). The metaphor "ANGER IS FIRE" is used to illustrate how metaphorical expressions in Uzbek reflect deep conceptual structures. Drawing on research in cognitive science and neuroscience, the article supports the idea that metaphor is not merely a linguistic device but a fundamental component of human thought and cognition.
Keywords: Phraseological units, conceptual metaphors, cognitive linguistics, uzbek language, linguistic worldview, Euphemism, conceptual mapping